Предмет: Алгебра,
автор: amakaor
Производная. Помогите сделать верхний под 7).... и 2 задание
Приложения:
![](https://files.topotvet.com/i/7e8/7e81516d12395e656604f6d846301a7c.jpg)
Ответы
Автор ответа:
0
7)
![y= sqrt[8]{-5+2x}=(2x-5)^{ frac{1}{8} } \ y'=frac{1}{8}(2x-5)^{ frac{1}{8}-1 }*2=frac{1}{4}(2x-5)^{ -frac{7}{8}}= frac{1}{4sqrt[8]{(2x-5)^7}} y= sqrt[8]{-5+2x}=(2x-5)^{ frac{1}{8} } \ y'=frac{1}{8}(2x-5)^{ frac{1}{8}-1 }*2=frac{1}{4}(2x-5)^{ -frac{7}{8}}= frac{1}{4sqrt[8]{(2x-5)^7}}](https://tex.z-dn.net/?f=y%3D++sqrt%5B8%5D%7B-5%2B2x%7D%3D%282x-5%29%5E%7B+frac%7B1%7D%7B8%7D+%7D++%5C+y%27%3Dfrac%7B1%7D%7B8%7D%282x-5%29%5E%7B+frac%7B1%7D%7B8%7D-1+%7D%2A2%3Dfrac%7B1%7D%7B4%7D%282x-5%29%5E%7B+-frac%7B7%7D%7B8%7D%7D%3D+frac%7B1%7D%7B4sqrt%5B8%5D%7B%282x-5%29%5E7%7D%7D+)
2a) f(x)=x⁻³
f'(x)=-3x⁻⁴
f'(3)=-3*3⁻⁴=-3⁻³=-1/27
2б)
![f(x)= sqrt{3-2x}=(3-2x)^{ frac{1}{2} } \f'(x)=frac{1}{2}(3-2x)^{ frac{1}{2}-1 }*(-2)=- (3-2x)^{ -frac{1}{2} } = -frac{1}{ sqrt{3-2x} } f(x)= sqrt{3-2x}=(3-2x)^{ frac{1}{2} } \f'(x)=frac{1}{2}(3-2x)^{ frac{1}{2}-1 }*(-2)=- (3-2x)^{ -frac{1}{2} } = -frac{1}{ sqrt{3-2x} }](https://tex.z-dn.net/?f=f%28x%29%3D+sqrt%7B3-2x%7D%3D%283-2x%29%5E%7B+frac%7B1%7D%7B2%7D+%7D+%5Cf%27%28x%29%3Dfrac%7B1%7D%7B2%7D%283-2x%29%5E%7B+frac%7B1%7D%7B2%7D-1+%7D%2A%28-2%29%3D-+%283-2x%29%5E%7B+-frac%7B1%7D%7B2%7D+%7D+%3D+-frac%7B1%7D%7B+sqrt%7B3-2x%7D+%7D+)
![f'(-11)=-frac{1}{ sqrt{3-2(-11)} }=-frac{1}{ sqrt{3+22} }=-frac{1}{ sqrt{25} }=- frac{1}{5} f'(-11)=-frac{1}{ sqrt{3-2(-11)} }=-frac{1}{ sqrt{3+22} }=-frac{1}{ sqrt{25} }=- frac{1}{5}](https://tex.z-dn.net/?f=f%27%28-11%29%3D-frac%7B1%7D%7B+sqrt%7B3-2%28-11%29%7D+%7D%3D-frac%7B1%7D%7B+sqrt%7B3%2B22%7D+%7D%3D-frac%7B1%7D%7B+sqrt%7B25%7D+%7D%3D-+frac%7B1%7D%7B5%7D+)
2a) f(x)=x⁻³
f'(x)=-3x⁻⁴
f'(3)=-3*3⁻⁴=-3⁻³=-1/27
2б)
Похожие вопросы
Предмет: Биология,
автор: sashadu737
Предмет: Литература,
автор: ivanovamakinsk
Предмет: Математика,
автор: Аноним
Предмет: Алгебра,
автор: nastya13333333
Предмет: Математика,
автор: aybekkurmanov